2007
DOI: 10.1140/epjd/e2007-00269-3
|View full text |Cite
|
Sign up to set email alerts
|

Electron capture into few-electron heavy ions: Independent particle model

Abstract: Abstract. We apply the density matrix theory to re-investigate the radiative electron capture into heavy ions with one valence electron. Attention has been paid particularly to the magnetic sublevel population of the residual ions, as described in terms of alignment parameters. Simple method, based on an independent particle model, which takes into account the Pauli principle, is proposed for evaluating the alignment of the excited ionic states. By making use of this method, detailed calculations are performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…For highly charged ions, both the bound-bound and boundfree radiative electron transitions are usually well described by the IPM [40]. In this model the many-electron wave functions are simply approximated by single Slater determinants as obtained from the hydrogenic orbitals in order to take the Pauli principle into account.…”
Section: B Independent Particle Modelmentioning
confidence: 99%
“…For highly charged ions, both the bound-bound and boundfree radiative electron transitions are usually well described by the IPM [40]. In this model the many-electron wave functions are simply approximated by single Slater determinants as obtained from the hydrogenic orbitals in order to take the Pauli principle into account.…”
Section: B Independent Particle Modelmentioning
confidence: 99%
“…In the high-Z domain, however, the structure of few-electron ions can already be reasonably well understood within the independent particle model (IPM). This model is well justified for heavy species especially, since the interelectronic effects scale with 1/Z and, hence, are much weaker than the electron-nucleus interaction [25,26,37]. Within the IPM, which takes the Pauli principle into account, the many-electron wave functions are approximated by means of Slater determinants, built from one-particle orbitals.…”
Section: B Evaluation Of the Reduced Transition Amplitudesmentioning
confidence: 99%
“…1s 21 S 0 photons can be traced back to the effective parameter b eff 2 . Since the same parameter defines also the anisotropy of the Ka 1 line, its evaluation has been discussed in detail before [10,12]. In particular, it was shown that for high-Z ions the alignment parameters A 2 ðJ b ¼ 1; 2Þ and the weights N 1,2 in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…1 S 0 electric dipole (E1) and 3 P 2 ? 1 S 0 magnetic quadrupole (M2) transitions, both of which contribute to the Ka 1 radiation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%